2009
DOI: 10.2329/perio.51.334
|View full text |Cite
|
Sign up to set email alerts
|

Smoking status and attitude to tobacco control policy among periodontists of the Japanese Society of Periodontology

Abstract: :The aim of this study was to investigate the smoking status and attitudes toward tobacco control among periodontists of the Japanese Society of Periodontology, a non-profit organization. The questionnaires to determine the smoking status and attitude towards the tobacco control policy were mailed to 861 periodontists. Four hundred thirty-five of them(53.3%), of whom 70.3% were in their 40s and 50s, returned the completed questionnaire. The respondents were divided into university staff(27.8%), university hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, this needs to be interpreted with caution, since nearly two-thirds of the participants were women. The overall prevalence of smokers was higher than that (14.7%) reported for the certified periodontists [25]. Tobacco-using health professionals, including dentists, were reported to be less proactive than their non-using counterparts [15,28-30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this needs to be interpreted with caution, since nearly two-thirds of the participants were women. The overall prevalence of smokers was higher than that (14.7%) reported for the certified periodontists [25]. Tobacco-using health professionals, including dentists, were reported to be less proactive than their non-using counterparts [15,28-30].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacies of smoking-cessation intervention in dental or medical-dental settings were shown in Japan [ 4 , 17 ], suggesting the feasibility of integrating dentists and dental hygienists in a medical smoking cessation intervention. Encouragingly, in a recent survey study of 435 certified periodontists of the Japanese Society of Periodontology, a relatively high percentage (54.7%) of the participants indicated that they provide some form of smoking cessation care to their patients [ 25 ]. Initiatives are needed to further promote smoking cessation care in our practice setting.…”
Section: Discussionmentioning
confidence: 99%